Autoantibodies against calcitriol in systemic lupus erythematosus – preliminary report - Bogaczewicz, Jarosław; Sysa-Jędrzejowska, Anna; Ząbek, Jakub; Kontny, Ewa; Woźniacka, Anna (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction. In patients with systemic lupus erythematosus (SLE) vitamin D deficiency is a frequent problem. Renal insufficiency, treatment with corticosteroids or antimalarials and photoprotection are regarded as the main causes of vitamin D deficiency. To date the role of antibodies directed against calcitriol in this process is not completely elucidated. Objective. To determine the frequency of occurrence of antibodies against calcitriol in patients with SLE. Material and methods. The study covered 37 patients with SLE and sera obtained from 30 healthy blood donors as a control. In the determination of autoantibodies against calcitriol, an immunoenzyme assay was used. Results. Autoantibodies directed against calcitriol were found in 3 (8.1%) patients with SLE. The study did not reveal a significant difference in the concentration of calcidiol (25(OH)D3) between SLE patients with and without autoantibodies directed against calcitriol. Conclusions. Autoantibodies against calcitriol do exist in SLE patients, but they do not influence the calcidiol level.